1990
DOI: 10.1002/joc.3370100106
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Thermal Changes Over the Indian Region Prior to the Monsoon Onset as Observed by Satellite Sounding Data

Abstract: The differential heating of the continents and the adjoining oceans is the primary cause for the summer monsoon circulation over South Asia. Two important synoptic climatological features associated with this are: the thermal heat low centred over Pakistan and adjoining areas; and the upper tropospheric high over the Tibetan Plateau. These two aspects relating to the onset phase of the monsoon are examined utilizing: (i) the data from the National Oceanic and Atmospheric Administration polar-orbiting satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…In general, the South Asian summer monsoon is associated with two important synoptic features: 1) the Tibetan high aloft in the upper troposphere over the plateau of Tibet (Flohn 1957), and 2) a heat low over the area extending from Somalia across southern Arabia to Pakistan and northwestern India including the Aravalli mountain ranges (Sajjad 2011;Joshi et al 1990). In the present study, the two features are found to be sensitive to the premonsoonal soil moisture condition.…”
Section: A Spatial Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the South Asian summer monsoon is associated with two important synoptic features: 1) the Tibetan high aloft in the upper troposphere over the plateau of Tibet (Flohn 1957), and 2) a heat low over the area extending from Somalia across southern Arabia to Pakistan and northwestern India including the Aravalli mountain ranges (Sajjad 2011;Joshi et al 1990). In the present study, the two features are found to be sensitive to the premonsoonal soil moisture condition.…”
Section: A Spatial Distributionmentioning
confidence: 99%
“…The higher gain in region W compared to region E is as a consequence of a lower moisture influx amount in region W. The results in the region N yield relatively high regional recycling ratios b of around 0.09 (CTL), which arises because the moisture influx is low and the TABLE 2. Changes in areal averaged (JJAS;1990 water budgets, single precipitation process terms, and the monsoon onset dates (Onset) for each analysis domain between the perturbed and the control simulations. The efficiency effect, remote effect, and surface effect as defined in Eq.…”
Section: October 2012 a S H A R A F E T A Lmentioning
confidence: 99%
“…It has been proposed by various researchers that the onset date could be predicted in terms of antecedent circulation (Kung andSharif 1980, 1982), moisture (Kumar 2004;Simon et al 2006), thermal features (Joshi et al 1990;Luo and Yanai 1984), and premonsoon thunderstorm activity (Ghanekar et al 2003). Several studies have reported on the prediction of the onset date of the summer monsoon over India using statistical methods (Ghanekar et al 2003;Pai and Rajeevan 2009;Raju et al 2007;Ramesh et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed characterization of inter tropical convergence zone has been carried out using satellite data. The INSAT and NOAA data have brought out unique nature of monsoon onset with large-scale changes in wind and moisture profiles in lower troposphere prior to monsoon onset 14,15 . The critical role-played by sea surface temperature in Indian Ocean and Pacific Ocean regions were clearly brought out by several studies.…”
Section: Weather and Climatementioning
confidence: 99%